ADHD and executive functioning deficits in OCD youths who hoard. (November 2016) - Park, Jennifer M.; Samuels, Jack F.; Grados, Marco A.; Riddle, Mark A.; Bienvenu, O. Joseph; Goes, Fernando S.; Cullen, Bernadette; Wang, Ying; Krasnow, Janice; Murphy, Dennis L.; Rasmussen, Steven A.; McLaughlin, Nicole C.; et al.
Abstract: Hoarding is common among youth with obsessive compulsive disorder (OCD), with up to 26% of OCD youth exhibiting hoarding symptoms. Recent evidence from adult hoarding and OCD cohorts suggests that hoarding symptoms are associated with executive functioning deficits similar to those observed in subjects with attention deficit hyperactivity disorder (ADHD). However, while hoarding behavior often onsets during childhood, there is little information about executive function deficits and ADHD in affected children and adolescents. The study sample included 431 youths (ages 6–17 years) diagnosed with OCD who participated in the OCD Collaborative Genetics Study and the OCD Collaborative Genetics Association Study and completed a series of clinician-administered and parent report assessments, including diagnostic interviews and measures of executive functioning (Behavior Rating Inventory of Executive Functioning; BRIEF) and hoarding severity (Hoarding Rating Scale-Interview; HRS-I). 113 youths (26%) had clinically significant levels of hoarding compulsions. Youths with and without hoarding differed significantly on most executive functioning subdomains and composite indices as measured by the parent-rated BRIEF. Groups did not differ in the frequency of full DSM-IV ADHD diagnoses; however, the hoarding group had significantly greater number of inattention and hyperactivity symptoms compared to the non-hoarding group. In multivariate models, we found that overall BRIEF scores were related to hoarding severity, adjusting for age, gender and ADHD symptoms. These findings suggest an association between hoarding and executive functioning deficits in youths with OCD, and assessing executive functioning may be important for investigating the etiology and treatment of children and adolescents with hoarding and OCD.